Generic energy production model for smart grid emulation = Ogólny model producenta energii dla emulatora inteligentnych sieci energetycznych - Krysik, Miłosz; Piotrowski, Krzysztof; Rybski, Ryszard (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
This work describes the progress towards creating a model of energy production block to be applied in a smart grid emulator. This block allows reflecting the behavior of many energy production cases and by that enables defining multiple test scenarios for evaluating energy management Algorithms.
Keywords: inteligentne sieci energetyczne; emulator inteligentnych sieci energetycznych; model bloku producenta energii